Machining of metal matrix composites: effect of ceramic particles on residual stress, surface roughness and chip formation - Pramanik, Alokesh; Zhang, Liangchi; Arsecularatne, Joseph (ELSEVIER, 2008)
Machining forces, chip formation, surface integrity and shear and friction angles are important factors to understand the machinability of metal matrix composites (MMCs). However, because of the complexity of the reinforcement mechanisms of the ceramic particles, a fair assessment of the machinability of MMCs is still a difficult issue. This paper investigates experimentally the effects of reinforcement particles on the machining of MMCs. The major findings are: (1) the surface residual stresses on the machined MMC are compressive; (2) the surface roughness is controlled by feed; (3) particle pull-out influences the roughness when feed is low; (4) particles facilitate chip breaking and affect the generation of residual stresses; and (5) the shear and friction angles depend significantly on feed but are almost independent of speed. These results reveal the roles of the reinforcement particles on the machinability of MMCs and provide a useful guide for a better control of their machining processes.